2021
DOI: 10.21037/gs-20-857
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the Wisconsin and CaPTHUS indices for predicting multiglandular disease in patients with primary hyperparathyroidism in a southern European population

Abstract: Background: Focused parathyroidectomy is a safe technique for the treatment of primary hyperparathyroidism. The CaPTHUS score and the Wisconsin index are preoperative diagnostic tools designed to distinguish between single-and multigland disease. The aim of the study is to evaluate the usefulness of these models for predicting multiglandular disease in a European population.Methods: Retrospective review of a database of patients operated upon for primary hyperparathyroidism at a referral center. The sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…However, in this study, the Wisconsin Index was designed to decide whether to expect an intraoperative PTH value during parathyroidectomy and whether a more comprehensive exploration would be needed in parathyroidectomy, rather than the differential diagnosis of PHPT. In addition, two studies published in 2021 evaluated the usefulness of WIN in predicting monoglandular and multiglandular disease in PHPT, and it was shown that it is not as helpful as intraoperative PTH in predicting the multiglandular disease [ 18 , 19 ]. In this study, WIN was used for the first time for differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, the Wisconsin Index was designed to decide whether to expect an intraoperative PTH value during parathyroidectomy and whether a more comprehensive exploration would be needed in parathyroidectomy, rather than the differential diagnosis of PHPT. In addition, two studies published in 2021 evaluated the usefulness of WIN in predicting monoglandular and multiglandular disease in PHPT, and it was shown that it is not as helpful as intraoperative PTH in predicting the multiglandular disease [ 18 , 19 ]. In this study, WIN was used for the first time for differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…It can predict MGPD in those with positive imaging but is unreliable in patients with mild disease and low adenoma weight which are more common presentations of MGPD [15,31]. Whilst useful, [32], both the Wisconsin index and CaPTHUS score have been found to have variable sensitivity, specificity, positive and negative predictive values [33][34][35][36] and thus have not found universal acceptance and do not feature in national guidelines on the surgical management of hyperparathyroidism [37][38][39].…”
Section: Preoperative Imaging Of Parathyroid Glands In Mgpdmentioning
confidence: 99%
“…The Wisconsin Index (WIN) predicts the probability of additional hyperfunctioning glands during surgery and uses preoperative parathyroid hormone (PTH) levels and lesion weight during surgery ( 13 ). Their clinical values have been validated ( 14 , 15 ). However, neither of them can be used to improve the efficacy of MGD diagnosis preoperatively.…”
Section: Introductionmentioning
confidence: 99%